2015
DOI: 10.1080/01443410.2015.1024613
|View full text |Cite
|
Sign up to set email alerts
|

Dominant achievement goals across tracks in high school

Abstract: The dominant achievement goals (DAGs) of 7008 students in the third grade of Dutch secondary education (US grade 9) were investigated, based on Elliot & McGregors' 2 × 2 framework (2001), in relation to track-level and motivational variables. We found the mastery-approach goal and the performance-approach goal, generally considered adaptive, to be more prominent among students in lower tracks. In contrast, avoidance goals were more common in higher tracks. Most notably, in the highest track, the mastery-avoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 46 publications
4
18
0
2
Order By: Relevance
“…An alternative approach is to identify a person's dominant achievement goal (DAG), because in a specific context, persons tend to prefer one particular achievement goal over the other goals (Van Yperen, 2006). Generally, about 85% of the secondary school students have a DAG (Scheltinga et al, 2015). It has been found that individuals with different DAGs have distinct profiles which, generally, are in line with the extant empirical data concerning the traditional achievement goal approach (e.g.…”
Section: The Dominant Achievement Goalsupporting
confidence: 57%
See 4 more Smart Citations
“…An alternative approach is to identify a person's dominant achievement goal (DAG), because in a specific context, persons tend to prefer one particular achievement goal over the other goals (Van Yperen, 2006). Generally, about 85% of the secondary school students have a DAG (Scheltinga et al, 2015). It has been found that individuals with different DAGs have distinct profiles which, generally, are in line with the extant empirical data concerning the traditional achievement goal approach (e.g.…”
Section: The Dominant Achievement Goalsupporting
confidence: 57%
“…In the context of the Dutch secondary educational system with five ordered tracks, Scheltinga et al (2015) found a remarkably regular shift in prevalence pattern of the DAGs across tracks; both approach goals and the group without a DAG did become less, while both avoidance goals did become more prevalent in higher tracks, respectively. In addition, the changes along the valence dimension were far more pronounced than those along the definition dimension; the prevalence of the approach and of the performance goals decreased to 44.4% and 7.6%, respectively.…”
Section: Tracked Systems and Achievement Goalsmentioning
confidence: 97%
See 3 more Smart Citations